Environmental assessment of the near-net-shape electrochemical metallisation process and the Kroll-electron beam melting process for titanium manufacture - Dolganov, Aleksei; Bishop, Matthew T.; Tomatis, Marco; Chen, George Z.; Hu, Di (Royal Society of Chemistry, 2020)
The enforcement of environmental policies, in recent years, has become one of the major driving forces for industrial upgrading. Therefore, this study is focused on the evaluation of the environmental impact of a newly proposed titanium additive manufacturing process, including its in-depth comparison with the conventional method. This new method, referred to as Near-net-shape Electrochemical Metallisation, is based on the in-situ metallisation (via the FFC-Cambridge Process) of 3D-printed titanium oxide precursors (using Direct Ink Writing Process). In order to evaluate the main contributors to the environmental damage and to compare them with the conventional route for titanium manufacturing, the gate-to-gate Life Cycle Assessment has been conducted following established international standards. From this, the main contributors within the Near-net-shape Electrochemical Metallisation process were identified to be electricity and synthetic rutile, with medium impacts from argon and nickel. It was found that major impacts were challenging to be reduced without affecting the properties of the final product. However, the medium impacts can theoretically be modified, yielding potential improvements in the sustainability of the process by 10%. When compared to the conventional route (consisting of the Kroll Process, Free Fall Gas Atomisation and Electron Beam Melting), the end point results demonstrated that, by adopting the Near-net-shape Electrochemical Metallisation Process, the overall impact of titanium fabrication was dramatically reduced. Specifically, an average reduction of 68% for the ecosystem, human health and resources was observed.